Talent Management As A Basis Career Development In Implementing The Merit System - Ummu Azizah; Yuli Hasri; Laura Syahrul (Smart International Management Journal, 2024)
This research aims to determine the causes of the low aspect of career development for civil servants and the application of talent management strategies as a solution to career development problems. This research uses a qualitative method where the data collection technique is through interviews with 7 executive informants who are responsible and have authority over the career development of civil servants. Additional methods for collecting data are observation and documentation. The findings from the interview results in this research are that there are 6 out of 10 indicators of civil servant career development aspects that are not yet optimal, namely: Job Competency Standards documents, availability of employee profiles based on talent/competency mapping, talent pool implementation, availability of succession plans, qualification and competency gap documents, and capacity building and competency development. The results of the research findings show that the obstacles/constraints in the career development aspects analyzed from the 6 indicators are: bureaucratic politicization, lack of leadership commitment, budget allocation that is not yet optimal, and teamwork that still needs to be improved. The Talent Management Strategy can be a comprehensive solution in establishing the basis for future career development for civil servants.